The free vastus lateralis: and conjoined vastus lateralis anterolateral thigh/tensor fascia lata flap for oncological chest wall reconstruction - Falkner, Florian; Thomas, Benjamin; Mayer, Simon Andreas; Didzun, Oliver; Knoedler, Leonard; Panayi, Adriana C.; Hundeshagen, Gabriel; Vollbach, Felix Hubertus; Gazyakan, Emre; Kneser, Ulrich; Bigdeli, Amir Khosrow (Microsurgery, 2024)
Introduction A reconstructive option for extensive chest wall reconstruction is the free myocutaneous vastus lateralis muscle (VL) flap which can be performed in isolation or in conjunction with a fasciocutaneus anterolateral thigh (cVLALT) and/or myofasciocutaneous tensor fascia lata flap (cVLTFL). We aimed to directly compare the outcomes of these reconstructive options. Methods Patients who underwent oncological chest wall reconstruction with a free VL, cVLALT, or cVLTFL flap between February 2010 and 2022 were included in this retrospective study. Patient demographics, surgical characteristics, as well as medical and reconstructive outcomes, were evaluated. The operative outcomes between myocutaneous VL, cVLALT, and cVLTFL flap reconstructions were compared. Results A total of 41 patients underwent chest wall reconstruction with a free myocutaneous VL (n = 25; 61%), cVLALT (n = 14; 34%), or cVLTFL Three acute flap thromboses occurred in the entire cohort (3/41, 7%), with one myocutaneous VL flap failing because of recurrent venous thrombosis during the salvage procedure. Total flap necrosis was seen in two cases (5%; VL flap: n = 1; cVLALT flap: n = 1), and partial flap necrosis in one VL flap (1/25, 4%) and in the distal ALT portion of three cVLALT flaps (3/14, 21%). No significant difference was seen between isolated VL and conjoined VL flaps regarding the partial (p = .28) or total flap necrosis rate (p = .9). Conclusion The free (conjoined) VL flap provides reliable outcomes for obliterating dead space achieving durable reconstruction of complex chest wall defects.
Gesehen am 09.12.2024